Pengaruh Profitabilitas, Likuiditas dan Leverage Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Perusahaan Jasa Kontruksi Dan Bangunan Yang Terdaftar Di Bei Periode 2013-2022 - Afwan Habib; Desi Ika; Listiorini, Listiorini (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to see the impact of profitability, liquidity, leverage on profit growth with company size as a moderating variable. The population in this study is all Construction an Building Service Companies listed on the Indonesia Stock Exchange for the 2013-2022. The sampling method uses purposive sampling with a sample of 8 companies with 10 years of observation with a total of 80 observation data. This research data analysis method uses descriptive statistical analysis and a residual test approach in testing moderating variables. The research results state that profitability (tcount 3,764 > ttable 2,01290), liquidity (tcount 3,029 > ttable 2,01290) and leverage (tcount 4,026 > ttable 2,01290) have a positive and significant effect on profit growth. Company size is able to moderate the influence of profitability, liquidity and leverage on profit growth.